2014
DOI: 10.1111/febs.12791
|View full text |Cite
|
Sign up to set email alerts
|

Substrate scope and selectivity in offspring to an enzyme subjected to directed evolution

Abstract: We have analyzed the effects of mutations inserted during directed evolution of a specialized enzyme, Escherichia coli S-1,2-propanediol oxidoreductase (FucO). The kinetic properties of evolved variants have been determined and the observed differences have been rationalized by modeling the tertiary structures of isolated variants and the wild-type enzyme. The native substrate, S-1,2-propanediol, as well as phenylacetaldehyde and 2S-3-phenylpropane-1,2-diol, which are new substrates accepted by isolated varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…We have observed similar behavior, that is, apparent rate increase in laboratory‐evolved enzyme variants coupled with higher turnover values with a parallel raise in K M values, also in other alcohol dehydrogenases and hydrolases . Nonproductive binding (of a nonpreferred substrate isomer) may be a general phenomenon in substrate discrimination and promiscuity , with enantioselectivity as an extreme example.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…We have observed similar behavior, that is, apparent rate increase in laboratory‐evolved enzyme variants coupled with higher turnover values with a parallel raise in K M values, also in other alcohol dehydrogenases and hydrolases . Nonproductive binding (of a nonpreferred substrate isomer) may be a general phenomenon in substrate discrimination and promiscuity , with enantioselectivity as an extreme example.…”
Section: Resultssupporting
confidence: 68%
“…The resuspended samples were centrifuged at 12 270 g in a microcentrifuge for 5 min and subsequently transferred to HPLC glass vials together with reference samples. The amounts of ( R )‐ and ( S )‐ 1 were then analyzed by chiral HPLC (Chiralpack AS‐H, 250 × 4.6 mm Ø) using a n‐hexane/isopropanol (90 : 10 v/v) mixture as the mobile phase, a method adapted from . The system used an LC 20AD solvent delivery module (Shimadzu, Tokyo, Japan), a Shimadzu SIL‐10AF autosampler, and a Shimadzu SPDM20A photometric unit with a 0.5 mL·min −1 flow rate and 20‐min analysis time for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…We have, in ap arallel directed evolution effort, isolated an alcohol dehydrogenasev ariant of E. coli propane-1,2-diol oxidore-ductaseF ucO, dubbed DA1472. [13] DA1472 contains two point mutations (N151G, L259V) that renderi tv irtually inactive with (2S)-propane-1,2-diol, the natural substrate of FucO, [14] but highly active with 2.F urthermore, DA1472 does not accept secondary alcohols or ketones as substrates andt herefore does not act on aldol 1 either in oxidation or in reduction reactions. Hence, DA1472 exhibits all properties necessary for inclusion as ar eporter( coupling) enzyme for FSA-catalyzed cleavage of 1.…”
mentioning
confidence: 99%
“…The mutations introduced in substrate binding site of MFS transporters usually lead to a pronounced 10-fold K m alteration (Will et al, 1998;Sahin-Tóth et al, 1999). Among some previously described enzymes, S-1,2-propanediol oxidoreductase (FucO) alters its substrate specificity substantially upon just a single point mutation L 259 V in the substrate-binding site, while its K m increases just two-fold (Blikstad et al, 2014). In case of the higher eukaryotes, some mutated enzymes, it was shown that human galactokinase, point-mutated in its substrate-binding site (A 198 V), has K m only weakly altered (30% decrease) and its kinetic parameters are almost comparable to the wild type (Timson & Reece, 2003).…”
Section: Figure 6 Sulfate Uptake By the Strains Over-expressing Sb (mentioning
confidence: 99%